Arsitektur Rumah Adat Tradisional Mbatangu Di Kampung Ratenggaro - Sopiah Bela Winne; Frysa Wiriantari (Jurnal Anala, 2020)
Traditional Sumba houses not only have meaning arising from the belief system, but also have technical solutions that are able to solve architectural problems arising from the shape of the building. The Mbatangu traditional house in Ratenggaro village, known as the tower house, is divided into 3 parts, namely the lower part (kali kambunga), the middle part or (uma dei), and the upper part (uma deta). These three parts have an integrated structural system from the foundation to the roof structure system so that this traditional house can stand in a unique shape and become part of the cultural heritage of the people of Southwest Sumba. Especially the Mbatangu traditional house on the coast, which has a roof which is much higher than other traditional houses in mountainous areas.